Numerical and experimental study of a concentrated solar thermal receiver for a solar heating system with seasonal storage. (11th January 2021) - Li, Xiaoxia; Wang, Zhifeng; Li, Jinping; Chen, Longfei; Bai, Yakai; Yang, Ming; Guo, Minghuan; Sun, Feihu; Yuan, Guofeng
Summary: Solar heating systems are promising, reliable solutions for meeting heating demands, and reducing greenhouse gas emissions. Due to the temporal fluctuations of solar energy and the mismatch between solar energy availability and heating loads, the application of seasonal thermal storage for solar space heating has drawn much attention. Due to the significant reduction of the collection efficiency of flat plate collectors in the temperature range of 70‐95°C, the expansion of the application of concentrated solar thermal (CST) systems has aroused a strong interest. This study describes a demonstration project with a CST receiver designed for a solar heating system with seasonal storage. This work is to reveal the performance of the receiver in the middle and low‐temperature operation through experimental‐numerical approach using a one‐dimensional transient model with a non‐uniform flux distribution. The simulation results agreed well with experimental data for various operating conditions. The receiver had a collection efficiency of about 82% on a typical day. Meanwhile, the heat losses were mainly reflection losses followed by convection (about 5.6%) and radiation (about 2.1%). Additionally, the model was also used to investigate the effect of various operating parameters such as the inlet temperature, outlet temperature, and incident power on the collection efficiency and heat losses. Ultimately, the developed model and on‐site operating data are valuable for broadening the applications of CST receivers and further system simulation and optimization. Abstract : A pilot‐scale concentrated solar thermal system for space heating was introduced. A transient numerical model for solar receivers with non‐uniform flux distribution was developed. The performance of the receiver was analyzed by experimental‐numerical methods. The impacts of operational conditions on the performance of the receiver were studied.